On the treatment of hydroelastic slamming by coupling boundary element method and modal superposition method. (July 2021) - Feng, Song; Zhang, Guiyong; Wan, Decheng; Jiang, Shengchao; Sun, Zhe; Zong, Zhi
Highlights: The problem of hydroelastic slamming has been well simulated using a developed BEM-modal superposition coupled method. The proposed algorithm has the advantage of simulating complex fluid-structure interaction phenomenon in water entry with less CPU cost compared with NS solvers-FEM coupled method. Numerical results have shown the good performance of the present method as well as its potential for simulating hydroelastic slamming of wedges with both sides clamped or simply supported and entry water with constant vertical velocity. Abstract: An efficient fluid and structure interaction (FSI) coupling strategy between boundary element method, i.e. BEM (fluid part), and modal superposition method (structure part) is proposed to study hydroelastic slamming of wedge sections. The coupling strategy possesses simplicity in coding construction by transmission of coordinates, velocity and pressure on the fluid-solid interface. Convergence property of grid size, time step and modal number are first investigated. After that, the accuracy of the model is verified by comparing the numerical results with published ones. Hydroelastic effect associated with plate thickness, deadrise angle, impact velocity and boundary condition is discussed by the comparison between quasi-static, decoupling and coupling solutions, where quasi-static and decoupling solutions are established by neglecting the influence of elastic response of structure on the water flow field. The results show that quasi-static solution underestimates structural maximum response under specified hydroelastic parameters, and a time-lag effect is found between results of decoupling and coupling solutions.